Pemanfaatan Abu Sekam Padi Sebagai Bahan Pengganti Semen Pada Pembuatan Mortar di Desa Durian Dangkal Kabupaten Lahat - Barrorotul Azizah; Edowinsyah Edowinsyah; Fameira Dhiniati; Didi Ardiansyah; Vike Itteridi; Asep Syaputra (Pusat Riset dan Inovasi Nasional, 2023)
Durian Dangkal Village is a village that has abundant rice production which causes quite a lot of rice husk ash waste and has not been used for construction materials, rice husk ash which is usually only used as scouring ash and plant fertilizer. In this service activity, rice husk ash is used as a substitute for cement for the manufacture of geopolymer mortar. Geopolymer mortar is a mortar whose main material contains pozzolanic materials. The use of rice husk ash as a substitute for cement can reduce CO2 emissions and waste which can improve environmental quality. This service is carried out to increase public knowledge about waste processing which can be utilized in construction and has high selling power. The manufacture of geopolymer mortar was carried out by counseling and training methods which were directly demonstrated to the community and produced geopolymer mortar samples with cement as a substitute for rice husk ash.